(untitled) (UNWE Yearbook, 2009)
The paper reviews some of the economic aspects of Bulgaria’ welfare right before and after the accession to the EU. As an important milestone of the research stands the assumption that economic and social cohesion are closely interconnected, and that relation requires positive changes in the macroeconomic indicators i.e. GDP growth and macroeconomic stability to facilitate adequate changes in the incomes, spending and consumption of the populace. The paper establishes that the growth rates are a prerequisite for increasing the welfare; however, there is a clearly visible distance in between the growth rates and the direct private and public sources of welfare. That distance could cause a negative impact on the human and institutional growth-related factors. The authors refer to the evolving nature of irrational consumption structure associated with soaring exogenous effects and prerequisites for reiteration by following generations. Achieving sustainable welfare is linked to equitable distribution of incomes and overcoming extreme poverty and social exclusion. The market’ mechanisms which in many cases are the cause of welfare losses are not able to solve those problems. In those cases the state is the only corrective because it has the resources and the instruments needed for efficient intervention. This logic is consequential to the evolution of the economic welfare theory in which despite the presence of different paradigms, there exist comparatively unanimous position regarding the need for impartial redistribution. By analyzing the data from household budgets the authors arrive at the conclusion that the level of the matter-of-fact inequality is higher than the level usually ascertained by most commonly used indicators.The objective processes in the field of welfare reflect the subjective assessments of well-being. The authors quote data from polls and field studies which typify the Bulgarian citizens as the most unhappy and unsatisfied people among all other European nations, the cause of that being the differentiation between high expectations (mostly rooted in political rhetoric) and reality that changes always slower than expected.